2019
DOI: 10.1017/s0954579419000750
|View full text |Cite
|
Sign up to set email alerts
|

Influences of victimization and comorbid conditions on substance use disorder outcomes in justice-involved youth: A discrete time survival mixture analysis

Abstract: To understand how exposure to victimization during adolescence and the presence of comorbid psychological conditions influence substance use treatment entry and substance use disorder diagnosis from 14 to 25 years old among serious juvenile offenders, this study included 1,354 serious juvenile offenders who were prospectively followed over 7 years. Growth mixture modeling was used to assess profiles of early victimization during adolescence (14–17 years). Discrete time survival mixture analysis was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 85 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…This group had a relatively high probability of transitioning into either the poly‐substance use or alcohol and cannabis use classes. This finding is consistent with prior work on poly‐victimization (Davis, Dworkin, et al, 2019), which has found similarly small class of individuals experiencing multiple forms of victimization (between 5% and 15%) and are at increased risk for substance use (Davis, Christie et al, 2019; Davis, Janssen et al, 2019), mental health problems (Turner, Shattuck, & Finkelhor, 2015), and suicidal behaviors (Turner & Finkelhor, 2012). Finally, our findings suggest that young adults with depressive symptoms may be more susceptible to negative substance use outcomes associated with verbal aggression.…”
Section: Discussionsupporting
confidence: 90%
“…This group had a relatively high probability of transitioning into either the poly‐substance use or alcohol and cannabis use classes. This finding is consistent with prior work on poly‐victimization (Davis, Dworkin, et al, 2019), which has found similarly small class of individuals experiencing multiple forms of victimization (between 5% and 15%) and are at increased risk for substance use (Davis, Christie et al, 2019; Davis, Janssen et al, 2019), mental health problems (Turner, Shattuck, & Finkelhor, 2015), and suicidal behaviors (Turner & Finkelhor, 2012). Finally, our findings suggest that young adults with depressive symptoms may be more susceptible to negative substance use outcomes associated with verbal aggression.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of early theoretical and empirical work assessing effects of victimization on long-term outcomes has considered victimization in silos, investigating sexual abuse, physical abuse, or exposure to violence between parents, individually (Norman et al, 2012). However, more recently, poly-victimization theory asserts that individuals who experience multiple, or chronic, victimization types are more likely to report long-term behavioral and psychological problems, compared to any single victimization type (Davis et al, 2018; Davis, Janssen, et al, 2020; Finkelhor et al, 2007). When examining opioid misuse (defined as heroin use or nonmedical use of prescription narcotic medications), several studies have noted a dose–response relationship between victimization and opioid outcomes.…”
Section: Victimization and Substance Use: Theory And Empirical Evidencementioning
confidence: 99%
“…Nationwide, an estimated 172,000 (0.7%) adolescents aged 12-17 and 578,000 (1.7%) young adults aged 18-25 in the U.S. received substance use disorder treatment in the past year (Substance Abuse and Mental Health Services Administration, 2020). Adolescents and young adults in treatment present with a variety of complex problems, including victimization, dysfunctional family environments, comorbid mental health conditions, and criminal justice involvement (Chan et al, 2008; Davis et al, 2019; Tripodi & Bender, 2011). Unfortunately, in addition to these risk factors, some young people receiving treatment also report experiences of homelessness or housing instability (DiGuiseppi et al, 2020; Green et al, 2020).…”
Section: Age Sex and Sexual/gender Minority Status As Moderators Of T...mentioning
confidence: 99%